Mechanical Properties and Electrical Surface Charges of Microfibrillated Cellulose/Imidazole-Modified Polyketone Composite Membranes - Melo-Hurtado, F; Caballero-Alvial, L (Elsevier Ltd, 2020)
In the present work, microfibrillated cellulose (MFC) suspensions were produced by high-pressure homogenization and subsequently used to fabricate MFC membranes (C-1) by vacuum filtration followed by hot-pressing. A polyketone (PK50) was chemically modified by Paal-Knorr reaction to graft imidazole (IM) functional groups along its backbone structure. The resulting polymer is referred to as PK50IM80. By solution impregnation, C-1 was immersed in an aqueous solution of PK50IM80 and subsequently hot pressed, resulting in the fabrication of MFC/PK50IM80 composite membranes (C-IMP). Another method, referred to as solution mixing, consisted in adding MFC into an aqueous solution of PK50IM80 followed by vacuum filtration and hot-pressing to obtain MFC/PK50IM80 composite membranes (C-MEZC). C-IMP and C-MEZC were characterized by a wide range of analytical techniques including, X-ray photoelectron spectroscopy, Fourier-transform infrared chemical imaging, scanning electron microscopy, atomic force microscopy, dynamical mechanical analysis, tensile testing as well as streaming zeta potential, and compared to C-1 (reference material). The results suggested that C-IMP possess a more homogeneous distribution of PK50IM80 at their surface compared to C-MEZC. C-IMP was found to possess significantly enhanced Young s modulus compared to C-1 and C-MEZC. The tensile strength of C-IMP was found to improve significantly compared to C-1, whereas C-1 possessed significantly higher tensile index than C-IMP and C-MEZC. Furthermore, the presence of PK50IM80 at the surface of MFC was found to significantly shift the isoelectric point (IEP) of the membranes from pH 2.3 to a maximum value of 4.5 for C-IMP. Above the IEP, C-IMP and C-MEZC were found to possess significantly less negative electrical surface charges (plateau value of −25 mV at pH 10) when compared to C-1 (plateau value of −42 mV at pH 10). Our approach may have implication to broaden the range of filtration applications of MFC-based membranes. © 2020 Elsevier Ltd